THE EFFECT OF GREEN ACCOUNTING, GREEN INTELLECTUAL CAPITAL, CARBON EMISSION DISCLOSURE, AND TAX RISK ON FIRM VALUE - Anindia Vegi Aurora; Imas Kismanah (ZILLZELL MEDIA PRIMA, 2026)
This study examines the effect of green accounting, green intellectual capital, carbon emission disclosure, and tax risk on firm value in manufacturing firms listed on the IDX during 2021–2024. The research uses secondary data from annual and sustainability reports and applies panel data regression with the Random Effect Model. The results show that green accounting and green intellectual capital significantly affect firm value, while carbon emission disclosure and tax risk do not show a significant effect. Collectively, all variables significantly influence firm value. Overall, the findings indicate that environmental accounting practices and green-based intellectual capital contribute to improving firm value, whereas carbon disclosure and tax-related risk are not yet major determinants in investor valuation decisions.